Estrategias de e-marketing turístico para posicionar el hotel Márquez en la ciudad de Guaranda, provincia de Bolívar, año 2022. - Aucatoma Ruiz, Ibeth Rocio (2022)
With the development of tourism e-marketing strategies for the positioning of the Marquez hotel in the city of Guaranda, province of Bolívar, they applied the descriptive research methodology in order to describe the characteristics and functions of the departments of the establishment, it also allows us to describe characteristics of the problem of the object of study in order to delve into the population to investigate the concept of the subject of study, exploratory research in order to find all the information necessary for the development of the subject, the qualitative approach information was taken through interviews to the staff and the manager who are key actors within the establishment, direct observation we verify the services and facilities that the hotel has, with the bibliographic methods, observation and analysis was used for the analysis of the results and the development of the strategies of e-marketing, techniques and instruments The elements used were the primary sources, direct observation, the interview in order to obtain information in a broad and detailed way, the population and sample for this investigation were the manager and the employees of the hotel. As a result, we have found that there has been a low demand for clients due to the health crisis of covid -19 that paralyzed us all over the world, they do not have a defined organizational structure of the hotel, the clients that most arrive at the establishment are from the cities nearby such as Quito, Ambato and Guayaquil.